The teacher's role in the changing globalizing world : resources and challenges related to the professional work of teaching - Niemi, Hannele; Toom, Auli; Kallioniemi, Arto; Lavonen, Jari (Brill Sense, 2018)
The teacher's role is changing rapidly throughout the world. Traditional ways of working as a teacher are being challenged and teachers are faced with new areas of expertise they need to manage as educational professionals. These characteristics, challenges, and changes in the teacher's role have been identified internationally and are both conceptual and practical. Teachers' work now includes much more than teaching in classrooms and has expanded to designing new learning environments, collaboration and networking with others and mentoring colleagues. The Teacher's Role in the Changing Globalizing World addresses the significance of considering these issues, researching them, and emphasising the importance of actively influencing and protecting the parameters of the teacher role.